Urban sustainability on security of bottled drinking water and application of the law of negligence in Malaysia. - Razman, Muhammad Rizal; Azlan, Azrina; Md Jahi, Jamaluddin; Arifin, Kadir; Aiyub, Kadaruddin; Awang, Azahan (Wfl Publisher, 2011)
The law of negligence plays an important role in protecting individual from polluted and contaminated bottled drinking water in order to achieve urban sustainability. The use of the law of negligence in the area of an individual's protection is largely in reply to the necessity of each individual to protect his rights and interests in consuming bottled drinking water especially in urban area. Therefore, this paper will examine the use of the law of negligence in relation to the individual protection on the bottled drinking water safety from Malaysian laws point of view, identify actions and cases which deal with individual protection on polluted and contaminated bottled drinking water from the Malaysian legal perspectives and lastly, discuss the law of negligence as a means to protect individuals from polluted and contaminated bottled drinking water in Malaysia focusing on urban area.